2004
DOI: 10.1161/01.cir.0000126889.97626.b8
|View full text |Cite
|
Sign up to set email alerts
|

High-Density Lipoprotein and Cardiovascular Risk

Abstract: L ow serum levels of highdensity lipoprotein (HDL) are commonly encountered in patients with coronary artery disease (CAD). An example of this type of patient is a 42-year-old white man with a history of sudden-onset angina secondary to a 90% obstructive lesion along the proximal left anterior descending coronary artery. The family history was significant for his father, who died of a myocardial infarction (MI) at age 44 years. The patient underwent percutaneous transluminal angioplasty with stenting but devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
64
1
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(70 citation statements)
references
References 29 publications
2
64
1
3
Order By: Relevance
“…The difference in onset time of garlic on blood liquids may be caused by the different measured time and limited sample size in the study, thus enough courses of garlic administration may be crucial for blood liquid regulation. Low level of HDL is an independent risk factor for coronary artery disease, and increased level of HDL is protective against atherosclerotic disease [30]. Together with its confirmed anti-hypertensive effects, garlic was supposed to lower the risk of macrovascular and cardiovascular events in specific T2DM patients [9].…”
Section: Discussionmentioning
confidence: 99%
“…The difference in onset time of garlic on blood liquids may be caused by the different measured time and limited sample size in the study, thus enough courses of garlic administration may be crucial for blood liquid regulation. Low level of HDL is an independent risk factor for coronary artery disease, and increased level of HDL is protective against atherosclerotic disease [30]. Together with its confirmed anti-hypertensive effects, garlic was supposed to lower the risk of macrovascular and cardiovascular events in specific T2DM patients [9].…”
Section: Discussionmentioning
confidence: 99%
“…Although aerobic exercise did not alter the amount of HDL in the aerobic group, the lack of exercise in the control group showed significantly decreased HDL. A decrease in 10 mg HDL in the control group, according to the study of Toth, resulted in an increase of 13% in coronary heart disease (30). Constant HDL, in the exercise group, could be attributed to the normal range of the lipid profile.…”
Section: Discussionmentioning
confidence: 91%
“…[17]. High-density lipoproteins are recognized for their many atheroprotective functions [4]. It has also been implicated in the inhibition or the regression of atherosclerosis in humans and experimental animals [33].…”
Section: Discussionmentioning
confidence: 99%
“…CHD has a multi-factorial etiology, with many of the risk factors being influenced by lifestyle. Several prospective epidemiological studies have found that low level of serum high-density lipoprotein-cholesterol (HDL-C) constitute a strong, independent risk factor for coronary heart disease [3][4][5]. HDL protects against atherosclerosis by regulating cholesterol efflux from tissues, modulating inflammation, providing antioxidant, vasoprotective, antithrombotic and anti-infectious properties [6].…”
Section: Introductionmentioning
confidence: 99%